Europe-Central Asia Relations
XVIII, 270 p. 6 illus., 5 illus. in color.
Keywords: This book addresses the current state of economic and political development within Central Asia and the importance of European countries and organizations as international actors and supranational organizations for the Central Asian Region (CAR). It aims to provide a better understanding of Central Asia’s multi-faceted relations in rapidly evolving geostrategic dynamics and serves as a timely insight into the contours of Central Asian states’ policies, emerging trends, and significant features of these interactions. The aim is to analyze the main challenges for future between the Europe and Central Asia relations, to make recommendations for improvement, and to identify lines for future research on this matter. It highlights key aspects of current discourses in CAR vis-à-vis the role of European countries and China and other key players. It explores post-Soviet scenarios, considering recent drastic changes in the equation of international relations in general and, more particularly therole of Russia and China vis-à-vis Europe in the CARs. This book covers the different perspectives on the EU’s new strategy (2019), which will contribute to strengthening relations between the two growing regions. It will be beneficial for academics, practitioners, and policymakers.